Strangulated Hernia, a Persisting Surgical Emergency: Epidemiology and Management at Tengandogo University Hospital (Burkina Faso) - Rodrigue Namekinsba Doamba; Mamadou Windsouri; Jean Flores N‘doubare Sade; Faizah Rabo; Bazin Thony Lionel Traore; Adama Zebango; Aimee Florence Sanon; Ignace Imbe Yaro; Soukoula Stephane Corentin Zigani; Raweleguinbasba Armel Flavien Kabore; Adama Sanou (European Scientific Journal, ESJ, 2026)
Introduction: Strangulated hernia is a frequent and potentially serious surgical emergency that can be life-threatening. The objective of the study was to investigate the epidemiological, diagnostic, therapeutic and outcome aspects of patients managed for strangulated hernias.Materials and methods: This was a retrospective observational study with a descriptive and analytical purpose, conducted over a 10-year period from January 1, 2016 to December 31, 2025 at Tengandogo University Hospital.  Results: We collected 102 cases of strangulated hernia, accounting for 5% of surgically managed abdominal emergencies. The mean age of patients was 44 years, with a male predominance (sex ratio = 2.18). Manual laborers represented 44.1% of occupations. Clinically, all patients presented with a painful, irreducible swelling that was non-impulsive and non-expansive on coughing. Inguino-scrotal hernias were found in 43.1% of cases. Mesh repair was performed in 35.3% of patients. The small intestine was incarcerated in 46.1% of cases. The postoperative course was complicated in 7.8% of cases. Residual pain was reported in 14.7% of cases and recurrence was noted in 6.8% of cases. The Bassini technique was associated with residual pain (p = 0.0387), while the Mac Vay technique was associated with recurrence (p = 0.0496) ); however, this result should be interpreted with caution given the very small number of patients in this subgroup (n = 4).Conclusion: Reducing consultation delays and improving access to elective surgery are major challenges to limit these complicated forms. When they occur, mesh repair can be considered and is effective in the absence of any contraindication.